2015
DOI: 10.1007/s00417-015-3084-1
|View full text |Cite
|
Sign up to set email alerts
|

Short-term results of switchback from aflibercept to ranibizumab in neovascular age-related macular degeneration in clinical practice

Abstract: A short-term benefit of switchback from one anti-VEGF agent to another was observed in patients with nAMD who had shown no benefit from the initial switch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 22 publications
(47 reference statements)
2
16
0
3
Order By: Relevance
“…There are now emerging data on “switchback” cohorts, demonstrating that while switching may have an effect it may be limited in nature, and there are situations where switching back to an agent which was deemed ineffective in the past may actually produce clinically significant results. This was recently reported by Despreaux and colleagues in a study where 47 eyes with nAMD were switched back from aflibercept to ranibizumab demonstrating a short-term benefit of this switchback in patients who had shown no benefit from the initial switch from ranibizumab to aflibercept [ 43 ].…”
Section: Discussionmentioning
confidence: 67%
“…There are now emerging data on “switchback” cohorts, demonstrating that while switching may have an effect it may be limited in nature, and there are situations where switching back to an agent which was deemed ineffective in the past may actually produce clinically significant results. This was recently reported by Despreaux and colleagues in a study where 47 eyes with nAMD were switched back from aflibercept to ranibizumab demonstrating a short-term benefit of this switchback in patients who had shown no benefit from the initial switch from ranibizumab to aflibercept [ 43 ].…”
Section: Discussionmentioning
confidence: 67%
“…However, many studies have observed improved structural outcome of refractory cases when changing to a different anti-VEGF drug, mostly from ranibizumab or bevacizumab to aflibercept, 19 , 23 – 31 but recently also from aflibercept back to ranibizumab. 32 , 33 Although these reports are difficult to interpret in the absence of appropriate control arms, authors have considered the effect of tachyphylaxis/ drug tolerance, as well as the differences between the drugs, or the natural course of time on treatment. 24 , 34 The proposed mechanisms of improved efficacy after switching between two anti-VEGF drugs can be explained by different molecular sizes and the associated transport of molecules through the retina and into the subretinal space (ranibizumab compared to bevacizumab), higher binding efficacy, and a wider spectrum of action (aflibercept compared to both bevacizumab and ranibizumab).…”
Section: Introductionmentioning
confidence: 99%
“…In der Literatur findet man erst 1 Studie von Despreaux et al [17], welche die Effektivität einer Rückumstellung untersuchte. Verglichen mit dieser Studie zeigten sich in unserer Studie ähnliche Ergebnisse hinsichtlich der Reduktion der Netzhautdicke vor Therapieumstellung und nach Therapierückumstellung.…”
Section: Diskussionunclassified
“…Nach Therapierückumstellung zeigten sich unterschiedliche Visusverläufe. In der Studie von Despreaux et al [17] war eine signifikante Visusverbesserung zu beobachten mit einer durchschnittlichen Sehleistung über dem Ausgangsvisus vor Therapieumstellung. Dagegen konnte in der vorliegenden Studie zwar ebenfalls eine Visusverbesserung nach Rückumstellung beobachtet werden, der Ausgangsvisus wurde allerdings nicht wieder erreicht.…”
Section: Diskussionunclassified
See 1 more Smart Citation